(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper proposes an analysis of the business-to-government (B2G) data sharing mechanism envisaged by the Regulation EU 2023/2854, the so-called Data Act. The Regulation, in force since 11 January 2024, will be applicable from 12 September 2025, requiring the actors involved to put in place a compliance process. The focus of the paper is to present an assessment of the mechanism foreseen by the EU legislators, with the intention of highlighting two bottlenecks, represented by: (i) the flexibility of the definition of “exceptional need”, “public emergency” and “public interest”; (ii) the cumbersome procedure for data holders. The paper discusses the role that could be played by in-house data stewardship structures as a particularly beneficial contact point for complying with B2G data sharing requirements.